Family roles, challenges and needs in caring for traumatic brain injury (TBI) family members: a systematic review - Azlinda Azman; Nor Amalina Jali; Paramjit Singh Jamir Singh; Jafri Malin Abdullah; Haidi Ibrahim (Journal of Health Research, 2020)
Purpose – Advanced medical technology has reduced the mortality rate among traumatic brain injury (TBI) patients. This, however, has led to an increasing number of surviving patients with a major disability. As a consequence, these patients need attentive care which becomes an important issue for the society, particularly family members. Thus, this paper aims to review some of the salient roles, challenges and needs of the family caregivers in caring or nursing for their family members diagnosed with TBI. Design/methodology/approach – An inclusive search of the literature was undertaken to identify the family roles, challenges and needs in supporting and nursing TBI patients. Findings – Previous studies have shown that the family needs to address two important aspects of taking care of TBI patients, which involve emotional and physical affairs. Hence, it is essential for the family members to have adequate information on healing treatment, nursing and care methods, financial support, support groups, managing self-care and, more importantly, emotional and social support. Originality/value – This paper is not currently under consideration, in press or published elsewhere. In Malaysian culture, nursing disabled patients have always been a family responsibility. The role of nursing the patients has been done domestically and is considered a private affair. In order to execute the role, some put the patient needs as their priority and leave aside their needs and matters.